Manual de história da 5ª classe do ensino primário em Angola: uma análise à luz dos conceitos de negritude e decolonialidade - Monteiro, Cristiano José dos Santos (Universidade Federal de São Carlos, 2024)
This study analyzes the curricular content of the History Manual for the 5th grade of Primary Education in Angola, based on the concepts of blackness and decoloniality. It was guided by the following research questions: Is it possible to identify evidence of the ideals advocated by the Blackness Movement in the History Manual for the 5th grade of Primary Education in Angola? If so, what do such evidence reveal? What are the relationships between the content of the Manual and the concept of decoloniality? Its general objective was to: Analyze the curricular text interpreted by the History Manual for the 5th grade of Primary Education in Angola, in light of the concepts of blackness and decoloniality, in the context of the political emancipation of that country. And as specific objectives: To identify the social aspects present in the History Manual for the 5th grade of Primary Education in Angola; to identify the cultural aspects present in the History Manual for the 5th grade of Primary Education in Angola; to identify the political aspects present in the History Manual for the 5th grade of Primary Education in Angola; to analyze these results in light of the ideals of the Blackness Movement and the concept of decoloniality. Regarding the methodological aspects, this was a qualitative documentary research. The data were processed through a “thematic” content analysis. The results were presented according to thematic axes, namely: the social aspects showed the condition of Angolan society under colonial rule, marked by inequalities, highlighting the Portuguese administration’s neglect in guaranteeing access to public services for Angolans. The cultural aspects showed data on: the ethnic diversity of Angola, made up of peoples and kingdoms; the way they were socially organized, revealing what Angola was like before colonization; the characterization of the collections, monuments and cultural practices and values, peculiar elements of Angolan culture that keep alive the achievements of Angolan heroes and heroines. The political aspects explored the process of social construction through the struggle and efforts of different resistance groups and personalities among the peoples and kingdoms of Angola, culminating in the actions of the liberation movements, which created a collective consciousness of unity. We found that the Manual values Angolan identity by emphasizing the struggle for liberation from colonial rule. Given these data, there is strong evidence that the curricular content of the 5th grade History Manual is focused on emancipation and the rescue and preservation of Angolan identity, from the perspective of a historicity that defends the motto of Angola for Angolans. There is also evidence that the curricular content corresponds to the intentions of the Angolan government to improve the educational system by implementing educational reform. There is strong evidence that our initial hypothesis is confirmed, that the ideals of blackness would be contemplated in the Manual. We were able to confirm this by analyzing the results in light of the concepts of blackness and decoloniality. The research also revealed an affinity between its results and the concept of decoloniality, since it breaks with the colonizing logic of analyzing a specific African reality from the perspective of sources from the Global North.
History manual for 5th grade of primary education in Angola: an analysis in light of the concepts of blackness and decoloniality
Keywords: Negritude; Decolonialidade; Educação escolar em Angola; Currículo interpretado; Blackness; Decoloniality; School education in Angola; Interpreted curriculum; CIENCIAS HUMANAS::EDUCACAO::CURRICULO; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO